Specific detection of methicillin-resistant Staphylococcus species by multiplex PCR. - Vannuffel, P (1995)
In Staphylococcus aureus, mecA and femA are the genetic determinants of methicillin resistance. By using a multiplex PCR strategy, 310- and 686-bp regions of the mecA and femA genes, respectively, were coamplified to identify susceptible (lacking mecA) and resistant (mecA+) staphylococci and to differentiate S. aureus (femA+) from coagulase-negative staphylococci (lacking femA). A third staphylococcal genomic sequence, corresponding to IS431 and spanning 444 bp, was used as a PCR control. One hundred sixty-five staphylococcal strains were tested. All 72 methicillin-resistant strains were found to be mecA+, and 92 of the 93 susceptible isolates lacked mecA. Only one coagulase-negative Staphylococcus isolate carrying the mecA gene was highly susceptible to oxacillin. The femA determinant was a unique feature of S. aureus; it was found in 100% of the S. aureus strains tested but was undetectable in all of the coagulase-negative staphylococci tested. The possibility of directly detecting the mecA and femA genes in blood samples was also investigated. After two amplification steps, a sensitivity of 50 microorganisms per ml of freshly collected spiked blood was achieved. In conclusion, coamplification of mecA and femA determinants proved to be very reliable both for rapid detection of methicillin resistance and differential diagnosis between S. aureus and other staphylococci. This technique, which can be successfully performed with blood samples, could be a useful tool in the diagnosis and treatment monitoring of staphylococcal infections.